DC-STAMP activates the PI3K/AKT/mTOR signaling pathway to regulate PANoptosis in acute myeloid leukemia - Qian Liang; Biao Li; Yue Li; Longhui Ma; Li Dong; Ning Ding; Wei Zhang; Haoran Wang; Junying Liu (PLoS ONE, 2026)
Background PANoptosis is a newly defined form of programmed cell death that integrates features of apoptosis, pyroptosis and necroptosis, playing a critical role in immune regulation and tumor biology. Clinically, Acute Myeloid Leukemia (AML) patients with high DC‑STAMP expression exhibited notably poorer cytogenetic risk profiles and shorter overall survival. Gene set enrichment analysis of primary AML samples from public databases revealed significant enrichment of the mTORC1 signaling pathway, a core signaling axis regulating the apoptotic process, in AML samples with high DC-STAMP expression. Methods DC-STAMP knockdown and overexpression models were established in the AML cell line THP-1 using small interfering RNA (siRNA) and lentiviral plasmids, respectively. Western blotting and RT-PCR were used to assess changes in PI3K/AKT/mTOR pathway activity in response to altered DC-STAMP expression. Flow cytometry and other cellular phenotypic assays were employed to evaluate the impact of DC-STAMP on PANoptosis in AML cells. Finally, PI3K inhibitors were introduced to assess the functional reversal of DC-STAMP–driven malignant phenotypes through downstream PI3K pathway inhibition. Results High DC-STAMP expression in AML activated the PI3K/AKT/mTOR signaling pathway and suppressed the PANoptosis process, thereby enhancing leukemic cell survival and chemoresistance. In contrast, genetic silencing of DC-STAMP or pharmacological inhibition of downstream PI3K restored normal apoptotic processes and significantly attenuated the malignant phenotypes driven by mTOR hyperactivation. Conclusions Activation of DC-STAMP is an essential mechanism that suppresses PANoptosis and promotes chemoresistance in AML cells. Targeting the downstream PI3K/mTOR signaling pathway may offer a promising therapeutic strategy for this high-risk AML subtype.